Los Unitarios Faccionalismo, prácticas, construcción identitaria y vínculos de una agrupación política decimonónica, 1820-1852 - Zubizarreta, Ignacio (Historamericana, 2022)
In this work we try to deepen the knowledge about the behavior of Unitarianism, a faction that had a fundamental role in the political dynamics of the first half of the 19th century in Argentina.